Investigating a BIR-containing plasmodium falciparum protein and identifying its binding partners - Liebenberg, Dale (My University, 2018)
The majority of the worldwide malaria deaths are caused by the Plasmodium falciparum parasite and unfortunately parasite strains are emerging that are resistant to not only artemisinin, but also the partner drugs used in current antimalarial combination therapy. The intraerythrocytic P. falciparum life stage is characterised by exponential, asexual proliferation that could cause the premature death of the human host before the sexual gametocytes have had enough time to develop and be taken up by the mosquito vector to continue its lifecycle. It is hypothesised that P. falciparum maintains its population at a level low enough to allow for the transmission of these gametocytes by using a form of regulated cell death (RCD). The molecular members of this cell death pathway are currently unclear, but a putative P. falciparum inhibitor of apoptosis protein (PfIAP; PF3D7_0519600) has previously been identified. Metazoan IAP proteins play anti-apoptotic roles in cells by interacting and inhibiting pro-apoptotic caspases, but also perform other functions. Analysis of the PfIAP protein using bioinformatic tools revealed that it contains one conserved baculoviral IAP repeat (BIR) domain and that this P. falciparum BIR domain is structurally similar to the BIR domains of various human IAP proteins. mRNA extracted from asexual P. falciparum parasites was used to construct a biotin-tagged phage display library, which was used in biopanning experiments with two regions of the PfIAP protein, expressed as recombinant GST-tagged proteins. Four binding partners were identified for the N-terminal BIR domain of the protein, while two proteins were identified as interacting partners for the C-terminal region of PfIAP. Of these, a double C2-like domain-containing protein (PfDOC2) and the high molecular weight rhoptry protein 3 (PfRhopH3) were expressed as recombinant His-tagged proteins and verified as PfIAP binding partners by in vitro binding assays. Transgenic P. falciparum parasites were generated expressing a GFP-tagged PfIAP BIR domain, which localised to the cytoplasm under both normal and high temperature conditions which mimic febrile malaria, a physiological trigger of RCD. Knockout experiments of the pfiap gene using the CRISPR-Cas9 genome editing tool suggested that this gene could be essential for the survival of asexual P. falciparum parasites. This study offers the first details of a putative P. falciparum inhibitor of apoptosis protein and suggests that it could have non-apoptotic roles in the parasite, given the diverse functions of the binding partners that comprise the PfIAP protein-protein network.
A thesis submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy. Johannesburg, 2018.
Keywords: Malaria; Plasmodium falciparum